PENGARUH LINGKUNGAN KEWIRAUSAHAAN TERHADAP PENGEMBANGAN WIRAUSAHA DI KABUPATEN SLEMAN - Sri Haryani (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2017)
The emerge and growth of entrepreneurs are expected to reduce unemployment and increase the prosperity. The research objective is to analyze the effect of entrepreneurial environment (government policies and procedures, socio-economic conditions, skill of entrepreneurial and business, financial assistance, and non-financial assistance) to the growth of entrepreneurship. Entrepreneurial environment conducive expected to bring new entrepreneurs and develop existing entrepreneurs. Data were collected by a questionnaire distributed to 66 SMEs in Sleman. The sampling method using purposive sampling, while data analysis using SPSS 17.00. In this research, test instruments include the validity and reliability test, the results show that the entire statement item valid and reliable. Normality test, multicollinearity, and heteroscedasticity showed normal distribution of data, between independent variables does not occur multicollinearity problems, and found none problem heteroscedasticity. It can be concluded that the fators that affecting entrepreneurial growth in Sleman is socio-economic conditions, entrepreneurship and business skills, and financial assistance.